2015
DOI: 10.1088/1475-7516/2015/9/038
|View full text |Cite
|
Sign up to set email alerts
|

Testing SgrA*with the spectrum of its accretion structure

Abstract: Abstract. SgrA * is the supermassive black hole candidate at the center of the Galaxy and an ideal laboratory to test general relativity. Following previous work by other authors, we use the Polish doughnut model to describe an optically thin and constant angular momentum ion torus in hydrodynamical equilibrium and model the accretion structure around SgrA * . The radiation mechanisms are bremsstrahlung, synchrotron emission, and inverse Compton scattering. We compute the spectrum as seen by a distant observer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…[416,417] who calculated images and spectra for a toroidal accretion flow around a Kerr black hole in the model of Refs. [445][446][447], Reference [448] calculated spectra for the same torus model in the background of the Kerr-like metric of Ref. [64] and showed that such spectra can depend significantly on deviations from the Kerr metric.…”
Section: The Accretion Flow Of Sgr a *mentioning
confidence: 99%
See 1 more Smart Citation
“…[416,417] who calculated images and spectra for a toroidal accretion flow around a Kerr black hole in the model of Refs. [445][446][447], Reference [448] calculated spectra for the same torus model in the background of the Kerr-like metric of Ref. [64] and showed that such spectra can depend significantly on deviations from the Kerr metric.…”
Section: The Accretion Flow Of Sgr a *mentioning
confidence: 99%
“…Building on the work of [416,417] who calculated images and spectra for a toroidal accretion flow around a Kerr black hole in the model of [445][446][447][448] calculated spectra for the same torus model in the background of the Kerr-like metric of [64] and showed that such spectra can depend significantly on deviations from the Kerr metric. Figure 30 shows two sets of spectra for different values of the deviation parameter, where the black hole has fixed values of the spin = a r 0.5 g and inclination q =  60 and the torus has fixed values of the specific angular momentum of the fluid particles l = 0.3 or l = 0.6 (shown in the left and right panels, respectively), magnetic to total pressure ratio b = 0.1, electron to ion (corresponding to the maximum of the curve w M ( ), where ω is the frequency of the scalar field; see [449]) and ADM spin = a r 0.80 g using the accretion flow model of [416,417] with a fixed inner radius.…”
Section: The Accretion Flow Of Sgra *mentioning
confidence: 99%
“…The other goal of the EHT collaboration is the registration of the supermassive black hole M87* with the mass M = (6.6 ± 0.4) × 10 9 M ⊙ in the nearest to us giant elliptical galaxy M87 (NGC 4486), which is placed in the central part of the Virgo cluster of galaxies [93][94][95][96]. The technological levels of the EHT and similar projects BlackHoleCam [97] and GRAVITY [98,99] permit to reach the angular resolution that matches the event horizon size of these supermassive black holes and allow to get the black hole image [100][101][102][103][104][105][106][107][108][109][110][111][112][113].…”
Section: Introductionmentioning
confidence: 99%
“…There is another important diagnostic, namely, the accretion phenomenon around compact objects that has already been a very active field of research (see, e.g., [17][18][19][20][21][22][23][24][25][26][27]). The first comprehensive study of accretion disks using a Newtonian approach was made in [28].…”
Section: Introductionmentioning
confidence: 99%